Pengaruh Desain UI/UX Web multimedia terhadap Kepuasan Pengguna System dan Layanan Virtual UNPAB Menggunakan Metode Kuantitatif - Nurlela Pangaribuan; Abdul Khaliq; Supiyandi (Jurnal Nasional Teknologi Komputer, 2026)
This study aims to analyzze theeffect of User Interface (UI) and design on the level of user satisfaction in the virtual service system (Portal) UNPAB. The method used is a quantitative approach, with data collected through the distribution of questionnaires to portal users. The data were analyzed using SPSS software through several testing stages, namely validity testing, reliability testing, simple linear regression testing, t-test, and coefficient determination. The validity test results shows that all statement items in the UI/UX and user satisfaction variables are valid, as the calculated r-values are greater than the r table values. The reliability test results indicate that the Cronbach’s Alpha values are 0,716 for the UI/UX variable and 0,813 for satisfaction stated variables. That simple linear regression analysis resulted in the equation Y= 6,300 + 1,196X, which shows a significance value of 0,000 <0,05 and calculated t value of 16,165, thus it can be concluded that UI/UX design has a significant impact on user satisfaction, while the remaining 22,7% in influenced by other factors outside the study. Thus, it can be concluded that UI/UX design has a significant and strong effect in increasing user satisfaction on the UNPAB Portal.